Kandinsky or Me? How Free Is the Eye of the Beholder in Abstract Art?. (September 2019) - Braun, Doris I.; Doerschner, Katja
We investigated in "art-naïve" German and Chinese participants the perception of color and spatial balance in abstract art. For color perception, we asked participants (a) to adjust the color of a single element in 24 paintings according to their liking and (b) to indicate whether they preferred their version of the painting or the original. For spatial perception, we asked participants (a) to determine the "balance point" of an artwork and (b) to indicate their preferences for the original or left-right reversed orientation of previously seen and unfamiliar paintings. Results of the color experiments suggest that, even though the interactive task was of a rather open-ended nature, observers' color adjustments were not random but systematically influenced by each painting's color palette. Overall, participants liked their own color choices about as much as the original composition. Results of the spatial experiments reveal a remarkable consistency between participants in their balance point settings. The perceived lateral position of the balance point systematically affected the left-right orientation preference for a given painting. We conclude that "art-naïve" observers are sensitive to the composition of colors and spatial structures in abstract art and are influenced by their cultural backgrounds when experiencing abstract paintings.